Structural aspects in the theory of probability : a primer in probabilities on algebraic-topological structures - Heyer, Herbert (Series on multivariate analysis, 2004)
This book focuses on the algebraic-topological aspects of probabilitytheory, leading to a wider and deeper understanding of basic theorems, such as those on the structure of continuous convolution semigroupsand the corresponding processes with independent increments.